Mobile Charging Stations: A Comprehensive Review of Converter Topologies and Market Solutions - Rafael C. Neto; Camila M. Bandeira; Gustavo M. S. Azevedo; Leonardo R. Limongi; Márcio R. S. de Carvalho; José F. C. Castro; Pedro A. C. Rosas; Augusto C. Venerando; Newmar Spader; Emilio Bueno (Energies)
The adoption of electric vehicles (EVs) has shown exponential growth in recent years, with expectations for further development in the years to come. With such significant expansion, efforts and incentives are shifting from EV sales to projects aimed at expanding charging station infrastructure. In order to sustain this growing trend, a reliable and robust charging infrastructure is needed. However, the entire process of planning, designing, and constructing fixed charging stations (FCSs) is time-consuming and expensive. In this scenario, mobile charging stations (MCSs) offer a complementary solution to ensure the necessary reliability for the improvement of EV owners’ experiences in the electrified transportation sector, as they help reduce range anxiety, peak-hour costs, and waiting times. In this sense, this paper aims to disseminate the state-of-the-art research and studies on MCSs, covering topics such as architectures, standards, converter topologies, and market solutions.